A STUDY ON MENTORING PRACTICES FOR NOVICE TESL TEACHERS: A MALAYSIAN PERSPECTIVE - Jasmeet Kaur A/P Utumber Singh; Ainon Omar (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The study aims to examine the mentoring practices applied by TESL mentor teachers to support novice TESL teachers in secondary schools in the Malaysian context. The mentoring practices consist of five elements, Personal Attributes, System Requirements, Pedagogical Knowledge, Feedback and Modelling. This study also investigates the perception of TESL mentor teachers on the mentoring programme. This study employed both quantitative and qualitative method in data collection, which involved 40 Teaching English as Second Language (TESL) mentor teachers. The data collection instruments implemented are documented analysis of the course plan (Panduan Pembangunan Guru Baharu-PPGB 2015), semi-structured interviews and survey questionnaires. Based on the findings gathered, 95% of TESL mentor teachers opined that the mentoring programme for novice teachers is beneficial and crucial to assist novice TESL teachers. However, 5% of TESL mentor teachers remarked the mentoring programme as ineffective and not helpful to help novice TESL teachers in schools. The implication derived from this study is a mentoring programme for novice TESL teachers in really helpful and vital to support these novice TESL teachers to embark on their journey in schools. Thus, the mentoring programme should be strengthened and be updated all the time.